1988
DOI: 10.1155/1989/73481
|View full text |Cite
|
Sign up to set email alerts
|

Boron Particles Production inNonequilibrium Laser‐Chemical RadicalReactions During the IR MultiphotonDissociation of HCIC=CBCI2H Molecules

Abstract: The study of IR MPD of HCIC=CBCI2H molecule by CO2.-laser is presented. We provide experimental results showing high degree of fragmentation of this molecule (down to elementary boron) during nonequilibrium laser induced radical bimolecular reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The greatest interest is in modes of small particle production providing high dispersion and purity as well as the study of the processes of cluster conception and growth. Established theory and experiment have shown that elementary boron atoms group into an aggregate of icosahedrical form consisting of 12 boron atoms (B 12 ) [23,24]. Usually the boron small particles consist of one or more icosahedrons united in a cluster or various configurations depending on the thermodynamic conditions at formation.…”
Section: Nanostructures Of Wide Forbidden Zone Conductorsmentioning
confidence: 99%
“…The greatest interest is in modes of small particle production providing high dispersion and purity as well as the study of the processes of cluster conception and growth. Established theory and experiment have shown that elementary boron atoms group into an aggregate of icosahedrical form consisting of 12 boron atoms (B 12 ) [23,24]. Usually the boron small particles consist of one or more icosahedrons united in a cluster or various configurations depending on the thermodynamic conditions at formation.…”
Section: Nanostructures Of Wide Forbidden Zone Conductorsmentioning
confidence: 99%